Smokers' Behavior Following the Fatwa of the Indonesian Ulama Council - Ahmad Rasyid; Sobri, Sobri; Alfajri, Alfajri; Mustafa, Nurul Nadiah Binti; Az-zahra, Dwi Wahyuni; Intan, Nurul (Sekolah Tinggi Agama Islam Pengembangan Ilmu Al-Qur`an Sumatera Barat, 2024)
The Indonesian Ulama Council, as the highest authority issuing fatwas on Islamic law in Indonesia, has issued several fatwas concerning health and social behavior. One significant fatwa prohibits smoking in public places, reflecting concerns over its health impacts on both smokers and those exposed to passive smoking. This study aims to examine changes in smoking behavior following the issuance of the Indonesian Ulama Council fatwa, which prohibits smoking for pregnant women, children, and in public places. Employing a qualitative method with a case study approach, the research involves in-depth interviews and observations with six informants familiar with and affected by this phenomenon. All data are analyzed thematically using the Miles & Huberman interactive analysis model. The analysis reveals three categories of smokers post-fatwa: i) those who quit due to heightened awareness of smoking's dangers; ii) those who continue due to lack of awareness about the ban; and iii) those who persist due to perceived personal benefits from smoking, understanding the ban applies only to specific groups. This study underscores the need for enhanced education and socialization efforts regarding the fatwa and smoking cessation to promote broader compliance.